Efektivitas dan Variabilitas Stimulus Bergerak Versus Statis dalam Perimetri Glaukoma: Tinjauan Literatif - Dwiastri Iris Sarwastuti; Sri Kustantini Hendrastuti (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
Glaucoma is one of the leading causes of irreversible blindness worldwide, characterized by progressive damage to the optic nerve and visual field loss. Automated perimetry is an important method for detecting and monitoring the progression of glaucoma. However, conventional static perimetry has limitations, especially in advanced glaucoma cases where visual sensitivity is often below the threshold of detection. Moving stimuli have been proposed as an alternative or complementary method to overcome these limitations, by exploiting different visual mechanisms. This review aims to analyze the efficacy and variability of moving stimuli compared with static stimuli in glaucoma perimetry. A systematic literature review was conducted using four online databases: PubMed, Scopus, Google Scholar, and Cochrane. The PICO framework was used, with glaucoma patient population, intervention as moving stimuli, comparison with static stimuli, and outcomes evaluated including sensitivity, test-retest variability, and patient preference. The articles analyzed were published between 2011-2023, in English, and used study designs such as RCT, cohort, case-control study, or cross-sectional. Three relevant studies were found. Moving stimuli showed significant advantages in increasing sensitivity, especially in advanced visual field loss, extending the dynamic range to below 19 dB compared to static stimuli. Test-retest variability was also 44% lower with moving stimuli, indicating higher reliability. Most patients (62%) preferred moving stimuli due to greater comfort. However, there are limitations such as generalizability of results to a broader clinical population and the need for an updated normative database. Moving stimuli have significant advantages in glaucoma perimetry, including increased sensitivity, reduced variability, and better patient preference. These results demonstrate the potential of moving stimuli as an alternative or complementary method to static perimetry in the diagnosis and monitoring of glaucoma. Further studies are needed for validation in a broader clinical population as well as integration of moving stimuli into automated perimetry systems.